International multicentre observational study to assess the efficacy and safety of a 0·5 mg kg−1 per day starting dose of oral corticosteroids to treat bullous pemphigoid. (2nd September 2021) - Hébert, V.; Bastos, S.; Drenovska, K.; Meijer, J.; Ingen‐Housz‐Oro, S.; Bedane, C.; Lunardon, L.; Debarbieux, S.; Jedlickova, H.; Caux, F.; Chaby, G.; D'Incan, M.; et al.
Summary: Background: European guidelines propose a 0·5 mg kg −1 per day dose of oral prednisone as initial treatment for bullous pemphigoid (BP). We assessed the safety and efficacy of this regimen depending on BP extent and general condition of the patients. Methods: In a prospective international study, we consecutively included all patients diagnosed with BP. Patients received a 0·5 mg kg −1 per day dose of prednisone, which was then gradually tapered 15 days after disease control, with the aim of stopping prednisone or maintaining minimal treatment (0·1 mg kg −1 per day) within 6 months after the start of treatment. The two coprimary endpoints were control of disease activity at day 21 and 1‐year overall survival. Disease severity was assessed according to the Bullous Pemphigoid Disease Area Index (BPDAI) score. Results: In total, 198 patients were included between 2015 and 2017. The final analysis comprised 190 patients with a mean age of 80·9 (SD 9·1) years. Control of disease activity was achieved at day 21 in 119 patients [62·6%, 95% confidence interval (CI) 55·3–69.5]; 18 of 24 patients (75%, 95% CI 53·3–90·2), 75 of 110 patients (68·8%, 95% CI 59·2–77·3) and 26 of 56 patients (46.4%, 95% CI 33·0–60·3) had mild, moderate and severe BP, respectively ( P  = 0·0218). A total of 30 patients died during the study. The overall Kaplan–Meier 1‐year survival was 82·6% (95% CI 76·3–87·4) corresponding to 90·9%, 83·0% and 80·0% rates in patients with mild, moderate and severe BP, respectively ( P  = 0·5). Thresholds of 49 points for BPDAI score and 70 points for Karnofsky score yielded maximal Youden index values with respect to disease control at day 21 and 1‐year survival, respectively. Conclusions: A 0·5 mg kg −1 per day dose of prednisone is a valuable therapeutic option in patients with mild or moderate BP whose general condition allows them to be autonomous. Abstract : What is already known about this topic? Superpotent topical corticosteroids are the gold standard treatment for bullous pemphigoid (BP), whatever the severity. High doses of oral corticosteroids are effective but poorly tolerated in patients with BP. Medium doses of oral corticosteroids are effective in paucibullous BP, but their efficacy in severe forms has not yet been assessed. What does this study add? Medium doses of oral corticosteroids have poor efficacy in severe BP. A baseline Bullous Pemphigoid Disease Area Index score < 50 and a Karnofsky score ≥ 70 are predictors of treatment efficacy and low mortality, respectively. Linked Comment:  H.Y. Lee. Br J Dermatol 2021; 185 :1093–1094 .